Correction to: The Thioredoxin Fold Protein tfp2 from Extreme Acidophilic Leptospirillum Sp. Cf-1 Is a Chaperedoxin-Like Protein That Prevents the Aggregation of Proteins Under Oxidative Stress (International Journal of Molecular Sciences, 2024 25 13 6905 10.3390/Ijms25136905) - Levican-Jaque, G; Mascayano-Collado, C; Muñoz-Villagran, C; Acevedo-Arbunic, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Susanne Sievers and Daniela Zühlke were not included as authors in the original publication [1]. These authors contributed to the published research article by performing the proteomics experiments shown in the manuscript (Section 2.5, Table 1). These authors were missing from the published version due to a communication error made by the authors during the final stages of manuscript preparation. Due to the addition of these missing authors, a new institution, “Department of Microbial Physiology and Molecular Biology, Institute of Microbiology, University of Greifswald, 17489 Greifswald, Germany”, has also been added to the affiliation list. The corrected Author Contributions statement appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated. © 2024 by the authors.